Plutella polaris Zeller, 1880 (Lepidoptera, Plutellidae) rediscovered at Svalbard, Norway, with comments on its taxonomic position - Geir Søli; Leif Aarvik; Trude Magnussen (Nota Lepidopterologica, 2018)
After 142 years, Plutella polaris Zeller, 1880 was rediscovered at Svalbard, Norway, in 2015. The locality and its vegetation are described. The specimen is the first female ever recorded, and its genitalia are illustrated. The taxonomic position of P. polaris relative to other Plutella Schrank, 1802 species in the Northern hemisphere is discussed.